State and problems of establishment of comprehensive plans for spatial development of land use of territories of territorial communities - Tretiak, A.; Tretiak, V.; Priadka, T.; Tretiak, R.; Komarova, N. (Land Management, Cadastre and Land Monitoring, 2022)
Analysis of the pilot project of the comprehensive plan for spatial development of the territory of Pisochyn territorial community showed that failure of incorporate the requirements of land legislation in the context of the formation of sustainable (balanced) land use does not improve environmental stability and capitalization of land use as components of its sustainability. It was proposed to make changes and additions to the legislation of Ukraine on components, structure and content of the comprehensive plan for spatial development of the territories of territorial communities, zoning of lands outside the settlements which differs significantly from urban planned, especially the categories of agricultural lands, nature reserves and nature protection lands and defense lands. Improving the components, structure and content of the comprehensive plan for spatial development of land use of the territories of territorial communities based on European experience will reduce the cost of its development by 2-3 times. This is especially important considering that the state budget includes 187, 7 million UAH of subventions for the development of 150 comprehensive plans for spatial development of the territories of territorial communities in 2022(or 1, 25 million UAH for 1 project). Prospects for further explorations consist in researching areas for improvement of components, structure and content of the comprehensive plan for spatial development of land use of the territories of territorial communities, especially about zoning of lands outside the settlements which significantly differs from urban zoning. Key words: comprehensive plan for spatial development of territory of communities, environmental stability, capitalization of land use.